Analysis of the influence of marketing environment factors on the development of non-Olympic sports in sports schools (on the example of sports tourism) - Nataliiya Sereda (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the degree of influence of factors of macro- and microenvironment on the development of sports tourism in Kharkiv region. Materials and Methods: the paper uses the methods of analysis of literary sources and documents, system and organizational analysis, methods of marketing analysis (PEST and SWOT analysis), methods of mathematical statistics. The study was conducted in 4 children and youth sports schools of Kharkiv region, where it is cultivated sports tourism, only 124 respondents. Results: the degree of dependence of the functioning and development of sports tourism from the marketing environment. Conclusions: sport tourism is a relatively new socio-economic phenomenon. Promotion of non-Olympic sports, develop relevant marketing programs for their development is necessary to attract more children and teenagers to a systematic practice of physical fitness and sports activities.